Cats vs. Dogs: The Efficacy of Feliway FriendsTM and AdaptilTM Products in Multispecies Homes - Prior, Miriam Rebecca; Mills, Daniel Simon (Frontiers in Veterinary Science, 2020)
7% of UK households are estimated to own both a cat and a dog, despite a popular view that the two do not live well together. This is the first study to evaluate the effects of pheromone products Feliway FriendsTM and AdaptilTM on cat-dog interactions, in homes where owners perceived the potential for improvement in the relationship between their cat and dog. A blinded parallel randomised trial design over a 6-week period was used to evaluate the effect of each of the two products on the total score of both undesirable and desirable interactions, with 17 participants in each group completing the trial. Both undesirable and desirable interaction scores showed significant linear contrasts over time (undesirable score decreased; desirable score increased). Undesirable interaction scores were significantly lower (with a very large effect size) during treatment compared with baseline. There were no significant differences between the two pheromone products in relation to these outcome measures. AdaptilTM and Feliway FriendsTM were both associated with a significant decrease in: dog chasing cat/cat runs away; cat hiding from dog; cat/dog staring at the other; and dog barking at cat. With AdaptilTM a significant increase was also seen in: friendly greeting and times spent relaxed in the same room. From baseline (Week 2) to the end of the study (Week 6) there was a significant improvement in owners’ perception of dog relaxation in those participants who received AdaptilTM and of cat relaxation in those participants who received Feliway FriendsTM. Similarity in the core chemical structure of the appeasing pheromones might explain the main effects, whilst different species-specific additions may explain the product-appropriate species-specific increases in relaxation scores. Specific behavioural improvements seen with AdaptilTM may reflect a greater calming of dogs in this group, reducing their interest in seeking interaction with cats in the same home and the tension in the cat as a result. In conclusion, both products appear to improve the cat-dog relationship and could potentially be used together for maximal effect. If selecting one product AdaptilTM may be preferable, unless there is a particular need to increase the cat’s relaxation.